(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Cardiovascular diseases are the primary cause of mortality globally, underscoring the necessity for realistic vascular models to aid in the development of endovascular devices and training for interventionalists. While 3D printing holds promise for generating anatomically accurate blood vessel models, there is limited information on how well 3D-printed materials can replicate the elastic characteristics of the aortic wall. Consequently, this work aims to characterize the stiffness of 3D-printed composite materials in relation to biological vascular tissue. The mechanical properties of homogeneous and composite 3D-printed multilayer samples, both with and without additional embedded helical structures were tested and compared to porcine aortic samples and values for human aortic tissue gleaned from literature. The 3D printing materials had a hardness of either Shore 30A or 70A, using Stratasys Agilus or a combination of Agilus and VeroClear. All samples were printed with a Stratasys J850 PolyJet 3D printer (Stratasys Ltd., Eden Prairie, Minnesota, U.S.A). Uniaxial tension tests were conducted on ring-shaped samples using a Galdabini Quasar 100 universal testing machine (Galdabini SPA, Cardano al Campo, Italy) equipped with a 50 N load cell. Samples were deformed at a rate of 500 mm/min until they reached 10% deformation of the initial diameter, simulating the strain experienced by aortic tissue in the body. The deformation results yielded stiffness values ranging from 1.16 N/mm to 4.83 N/mm for 3D-printed materials, while both porcine samples and healthy human aorta stiffness values from literature ranged from 0.22 N/mm to 0.45 N/mm. The homogeneous 30A material, as well as multilayered 30A and 70A materials lacking helical structures, neared the stiffness ranges of biological tissue. Although 3D-printed composite materials are generally stiffer than biological tissue, the 3D-printed materials in this work could be used to emulate diseased tissue, such as vasculature afflicted by atherosclerosis.